Measurement of the top quark pair production charge asymmetry in proton-proton collisions at root s=7 TeV using the ATLAS detector - Aad, G; Abajyan, T; Abbott, B; Abdallah, J; Khalek, SA; Abdinov, O; Aben, R; Abi, B; Abolins, M; AbouZeid, O; Abramowicz, H; Abreu, H; et al. (2014)
This paper presents a measurement of the top quark pair (tt̄) production charge asymmetry AC using 4.7 fb-1 of proton-proton collisions at a centre-of-mass energy √s = 7TeV collected by the ATLAS detector at the LHC. A tt̄-enriched sample of events with a single lepton (electron or muon), missing transverse momentum and at least four high transverse momentum jets, of which at least one is tagged as coming from a b-quark, is selected. A likelihood fit is used to reconstruct the tt̄ event kinematics. A Bayesian unfolding procedure is employed to estimate AC at the parton-level. The measured value of the tt̄ production charge asymmetry is AC = 0.006 ± 0.010, where the uncertainty includes both the statistical and the systematic components. Differential AC measurements as a function of the invariant mass, the rapidity and the transverse momentum of the tt̄- system are also presented. In addition, AC is measured for a subset of events with large tt̄ velocity, where physics beyond the Standard Model could contribute. All measurements are consistent with the Standard Model predictions.